Quarterly Economic Commentary, Summer 2011 - DUFFY, DAVID; DURKAN, JOSEPH; O'SULLIVAN, CORMAC (ESRI, 2011)
Research Bulletin 2011/2/1: The Macro-economic Impact of Changing the Rate of Corporation Tax, by Thomas Conefrey and John Fitz Gerald Research Bulletin 2011/2/2: The Banking Sector and Recovery in the EU Economy, by Ray Barrell, Tatiana Fic, John FitzGerald, Ali Orazgani and Rachel Whitworth Research Bulletin 2011/2/3: Should We Be Worried About Income Inequality in Ireland?, by Richard Layte Research Bulletin 2011/2/4: Investing in Child Health and Development: The Impact of Breastfeeding on Children's School Performance, by Cathal McCrory and Richard Layte
PUBLISHED
Dublin
Keywords: Economics